Factors that Influence the Use of Teledentistry in Indonesia During the COVID-19 Pandemic - Rasmidar Samad; Fuad Husain Akbar; Rini Pratiwi; Nur Aini (Association of Support to Oral Health Research (APESB), 2023)
Objective: Evaluate the factors that influence the use of teledentistry during the COVID-19 pandemic in Indonesia. Material and Methods: An analytical observational study with a cross-sectional design with 163 respondents was conducted. The factors of using teledentistry studied in this study were knowledge, attitudes, beliefs, technology, benefits, and needs. The original questionnaire was constructed in English, later translated into Bahasa Indonesia, and modified to conform with Indonesian. Data analysis used univariate and bivariate (Chi-square test). Results:Respondents who have used teledentistry were 23.3%, while respondents who have never used teledentistry were 76.7%. There is no relationship between knowledge about teledentistry and the use of teledentistry (p>0.05). There is no relationship between the use of teledentistry and knowledge (p>0.05), attitudes (p>0.05), and beliefs (p>0.05). Conclusion: There were no factors associated with the use of teledentistry. The most influencing factor is the benefit of using teledentistry, which can affect the increase in the use of teledentistry during the COVID-19 pandemic.